The platform will undergo maintenance on Sep 14 at about 7:45 AM EST and will be unavailable for approximately 2 hours.
2016
DOI: 10.1016/j.athoracsur.2016.01.046
|View full text |Cite
|
Sign up to set email alerts
|

Tracheostomy After Operations for Congenital Heart Disease: An Analysis of the Society of Thoracic Surgeons Congenital Heart Surgery Database

Abstract: Background: Information concerning tracheostomy after surgery for congenital heart

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

8
81
2

Year Published

2018
2018
2023
2023

Publication Types

Select...
3
2

Relationship

0
5

Authors

Journals

citations
Cited by 38 publications
(91 citation statements)
references
References 14 publications
(27 reference statements)
8
81
2
Order By: Relevance
“…These findings were not related to higher rates of prematurity, lower gestational weights, or younger gestational ages in this group. The findings of increased mortality in infants with CHD are similar to other studies evaluating tracheostomy in pediatric patients of all ages with cardiac disease . For example, Funamura et al reported 27.5% mortality in children with CHD at various periods of follow‐up, which was significantly higher than patients without cardiac disease.…”
Section: Discussionsupporting
confidence: 82%
See 4 more Smart Citations
“…These findings were not related to higher rates of prematurity, lower gestational weights, or younger gestational ages in this group. The findings of increased mortality in infants with CHD are similar to other studies evaluating tracheostomy in pediatric patients of all ages with cardiac disease . For example, Funamura et al reported 27.5% mortality in children with CHD at various periods of follow‐up, which was significantly higher than patients without cardiac disease.…”
Section: Discussionsupporting
confidence: 82%
“…For example, Funamura et al reported 27.5% mortality in children with CHD at various periods of follow‐up, which was significantly higher than patients without cardiac disease. Several other studies have evaluated in‐hospital mortality after pediatric tracheostomy and reported high rates of mortality in cardiac patients ranging from 22% to 40% . These studies include a wide age range of children, mostly 0‐18 years, with CHD who have various associated comorbidities.…”
Section: Discussionmentioning
confidence: 99%
See 3 more Smart Citations